STUDI PENGENDAPAN PERAK PADA LIMBAH FIXER YANG TELAH JENUH DENGAN METODE PEMBAKARAN DAN PENGENDAPAN NaOH DAN Na2S - Dita Kesumayadi; Heri Sutanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Research has been done in silver recovery in saturated fixer liquid. Silver recovery method that used in this research was sedimentation by using chemical material NaOH and Na2S. Aim of this research is to compare amount of mass of the result of sedimentation method in silver recovery using NaOH and Na2S. This research used NaOH and Na2S in 2 M concentration to saturated fixer liquid at 5 litre amount. Deposits included in koi then burned until 200-3000C of temperature to form two layers. The upper layer was removed homever the layers below let in the koi. Lower layer was burned back with a 400-6000C to remove the rest of the remaining impurities. When the temperature reaches 6000C, put it in a bucket of water in which that liquid will be solidified and acquired a silver metal. Result of The research have showed that silver which is produced in NaOH sedimentation method has 16 gram and 25 gram in using Na2S sedimentation method. Na2S is more profit because produce silver more than NaOH. Keywords : fixer, temperature, sedimentation method, NaOH, Na2S.